Inovasi Digital Di Pondok Pesantren Al-Quran Az Zayadiy Dalam Bidang Ekonomi dan Pendidikan - Mufidah, Inayah Syadza; Mulyani, Diah Suci; Damayanti, Arlinda; Irhami, Muhammad Naufal Hanif (Universitas Khairun, 2024)
Digital innovation has an important role in keeping up with the increasingly rapid progress of the times. To make the digitalization process more efficient and optimal, several innovations have been implemented. One of them is using digital cards as a payment method in the canteen and also as an attendance system. This digital card not only makes it easy to carry out payment transactions quickly and safely, but also makes it easier to record student attendance accurately and in real time. This change is a real action in updating the education system, with the hope that it will provide significant benefits for all elements in the school environment, including students, teachers and parents. This paper aims to understand the consequences of using digital cards as a payment method in canteens and in academic contexts. This research utilizes an exploratory method based on a qualitative approach. The method of collecting information is through an interview process. and using the SWOT analysis method (Strengths, Weaknesses, Opportunities and Threats) to evaluate the level of effectiveness of using digital cards in Islamic boarding schools. Research reveals that the application of digital technology has an important influence on the progress of management and learning processes at the Az-Zayadiy Islamic boarding school.